ASPEK –ASPEK HUKUM PERJANJIAN INTERNASIONAL DAN KAITANNYA DENGAN MOU HELSINKI - Maryati B (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2017)
The Helsinki 2005 Memorandum of Understanding (MoU) is a peace agreement that was made by the international law subjects upon the agreement between the states (Indonesia) and the rebel group (Free Aceh Movement - GAM).  However, there are some questions underlying this agreement. The first is whether the Helsinki MoU can be classified as an international agreement or not if it is viewed from the subjects who signed the agreement. The second issue is about the status of the parties who signed the MoU; whether it can be eliminated according tothe agreement rules or not. The last issue is due to the law consequences ifthose parties break the agreement during the implementation of the MoU. This studyused a qualitative research method. The primary data was collected through interviews and the secondary data was obtained through the library research. The data was analyzed by using descriptive analytical method that was written in the form of report.From the data analysis it is found that the MoU Helsinki is categorized as an international agreement which use a treaty contract that only applies to the parties who sign the agreement. Considering of this agreement that is signed by only two parties which bound by the agreement rules; so, the parties must not be eliminated. This is done in order to keep the agreement to be still in place and not extinct. Further, it is also found that if the infraction happens during the implementation of the agreement i.e break the local laws (qanun) and its derivatives; then, the inflicted party can prosecute the offender into the trial. They also can request for a detriment or ask for the correct implementation of the agreement as it is agreed upon the agreement. If the infraction does occur, it will put the agreement at risk and harm the MoU. It is suggested that the Indonesian government should implement the MoU as it is already stated in the agreement and also bring about the qanun that has been made by both parties. This is done as the way to keep the peace agreement still in place.